Hubungan Merokok dengan Konversi Sputum Penderita TB Paru Kasus Baru di RSUD Dr. Moewardi Surakarta - Yonisa, Zefania; Harsini, .; Primadewi, Novi (Nexus Kedokteran Klinik, 2013)
Background: Tuberculosis or TB is an infectious disease caused by Mycobacterium tuberculosis complex and still a major health problem in Indonesia. Smoking TB patients have a greater risk for treatment failure and persistent infection. This study aims to determine the relationship between smoking and sputum conversion among patients with new cases pulmonary tuberculosis in Dr. Moewardi Hospital, Surakarta. Methods:This study was an observational analytic cross sectional approach. Subjects were new cases of pulmonary TB patients who have completed the intensive phase of treatment in Dr. Moewardi Hospital from January 2010 until March 2013. Patients with new cases pulmonary TB interviewed with a questionnaire to determine their smoking history. Sputum examination results seen in TB Treatment Card 01. Results were analyzed by Chi-Square statistical test (Î± = 0.05). Results: Of the 49 samples, a total of 26 pulmonary TB patients were smokers and 23 samples of patients with pulmonary tuberculosis are not categorized as smokers. Sputum conversion occurs more frequently in non-smoking pulmonary TB patients than smokers with pulmonary TB. Chi Square statistical test results showed a significant relationship between smoking and sputum conversion among patients with new cases pulmonary TB with p = 0.03 (p <0.05). Conclusions: There is astatistically significant association between smoking and sputum conversion among patients with new cases pulmonary TB. Smoking has a risk that sputum conversion does not occur after 2 months intensive phase of TB treatment. Keywords: smoking, sputum convertion, pulmonary tuberculosisÂ